Penyelesaian Permasalahan Penjadwalan Aktivitas Proyek dengan Batasan Sumber Daya Menggunakan Metode Cross Entropy - Maria Krisnawati (Dinamika Rekayasa, 2014)
Project scheduling is essential to be planned before activities. Standard methods of project scheduling based on precedence constraints scheduling events and the assumption that resources are not unlimited capacity. But in fact the project activity has resource limits. The main objective is to minimize the total duration of the project with precedence constraints and resource constraints for all project activities. Many optimization methods are used to improve the quality of scheduling and speed up the calculation time. This paper proposed the use of Cross Entropy (CE) method to solve resource constraints project scheduling problem, as well as comparing the advantages and disadvantages between the CE methods with Differential Evolution (DE) method. The purpose CE method consist of four critical steps including generating a sample of random solution, calculating the performance according to the specific fitness function, selecting elite sample and finally updating the previous parameters to get a better sample in the next iteration. To speed up the computation time, in this study decrease the number of samples for each iteration in Cross Entropy algorithm. Numerical experiments with several data sets from the Project Scheduling library (PSPLIB) showed that CE can provide the optimal total duration of the project same as the DE with calculation time is faster than DE.